Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

If in ∆ABC , ∠C = 90° , CD⏊AB, CD = h, BC = a, CA = b and AB = c, prove that 1/h² = 1/a² + 1/b².​

If In ABC C 90 CDAB CD H BC A CA B And AB C Prove That 1h 1a 1b class=

Sagot :

Answer:

Step-by-step explanation:

Xét tam giác AHC và tam giác BAC có

góc AHC = góc BAC =90°

Góc C chung

Suy ra tam giác AHC đồng dạng với tam giác BAC

Suy ra AH×BC=AB×AC

Suy ra h.a=b.c

Suy ra h^2.a^2=b^2.c^2

Suy ra h^2.(b^2+ c^2 )=b^2.c^2

( áp dụng định lí pytago vào tam giác ABC)

Suy ra 1/h^2=c^2+ b^2/b^2.c^2

Suy ra 1/h^2=1/b^2+1/c^2

Step-by-step explanation:

[tex] \bf \underline{Given \:Question -} \\ [/tex]

In ∆ ABC, ∠C = 90°, CD ⏊ AB, CD =h, BC = a, CA = b, AB = c, Prove that

[tex] \sf \: \dfrac{1}{ {h}^{2} } = \dfrac{1}{ {a}^{2} } + \dfrac{1}{ {b}^{2} } [/tex]

[tex] \red{\large\underline{\sf{Solution-}}}[/tex]

Given that,

In ∆ABC, ∠C = 90° and BC = a, CA = b, AB = c

So, Area of ∆ ABC is given by

[tex]\rm :\longmapsto\: Area_{∆ABC} = \dfrac{1}{2} \times ab - - - (1)[/tex]

Also,

In ∆ ABC, CD ⏊ AB

So, Area of ∆ABC is given by

[tex]\rm :\longmapsto\: Area_{∆ABC} = \dfrac{1}{2} \times ch - - - (2)[/tex]

From equation (1) and (2), we get

[tex]\rm :\longmapsto\:\dfrac{1}{2}ab = \dfrac{1}{2}ch[/tex]

[tex]\rm :\longmapsto\:ab = ch[/tex]

[tex]\rm\implies \:\boxed{\tt{ c = \frac{ab}{h}}} - - - (3)[/tex]

Again, In right ∆ ABC

Using Pythagoras Theorem, we have

[tex]\rm :\longmapsto\: {a}^{2} + {b}^{2} = {c}^{2} [/tex]

On substituting the value of c, from equation (3), we get

[tex]\rm :\longmapsto\: {a}^{2} + {b}^{2} = {\bigg[\dfrac{ab}{h} \bigg]}^{2} [/tex]

[tex]\rm :\longmapsto\: {a}^{2} + {b}^{2} = \dfrac{ {a}^{2} {b}^{2} }{ {h}^{2} } [/tex]

can be rewritten as

[tex]\rm :\longmapsto\:\dfrac{ {a}^{2} + {b}^{2} }{ {a}^{2} {b}^{2} } = \dfrac{1}{ {h}^{2} } [/tex]

[tex]\rm :\longmapsto\:\dfrac{ {a}^{2}}{ {a}^{2} {b}^{2} } + \dfrac{ {b}^{2}}{ {a}^{2} {b}^{2} }= \dfrac{1}{ {h}^{2} } [/tex]

[tex]\rm\implies \:\boxed{\tt{ \frac{1}{ {a}^{2} } + \frac{1}{ {b}^{2} } = \frac{1}{ {h}^{2} }}}[/tex]

Hence, Proved.

▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬

MORE TO KNOW

1. Pythagoras Theorem :-

This theorem states that : In a right-angled triangle, the square of the longest side is equal to sum of the squares of remaining sides.

2. Converse of Pythagoras Theorem :-

This theorem states that : If the square of the longest side is equal to sum of the squares of remaining two sides, angle opposite to longest side is right angle.

3. Area Ratio Theorem :-

This theorem states that :- The ratio of the area of two similar triangles is equal to the ratio of the squares of corresponding sides.

4. Basic Proportionality Theorem:

If a line is drawn parallel to one side of a triangle, intersects the other two lines in distinct points, then the other two sides are divided in the same ratio.

Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.